2014
DOI: 10.2108/zsj.31.89
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cytogenetic Analysis of the Scleractinian CoralAcropora solitaryensisVeron & Wallace 1984

Abstract: We performed a molecular cytogenetic investigation of the scleractinian coral Acropora solitaryensis, which is dominant in the temperate region of Japan (30-35°N). Molecular cytogenetic analysis, using fluorescence in situ hybridization (FISH), was carried out for karyotyping and gene mapping. We propose the karyotype of this coral (2n = 30) based on C-banding and FISH analyses. FISH mapping of the rRNA gene was carried out with a probe generated by PCR amplification using rRNA gene primers. Furthermore, the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…Of the 1,430 HQ SNPs used for linkage analysis, we were able to assign most (87%) to linkage groups with high confidence (LOD scores ≥ 8). Most of the mapped markers (998, or 81% of mapped markers) were captured in the 16 largest linkage groups (LGs), a biologically plausible number comparable to the range of haploid chromosome numbers (n) reported in other Scleractinian corals (n = 14-27; [67][68][69]). Because chromosome numbers have not been directly determined in O. faveolata, we included all linkage groups containing sufficient markers to provide meaningful information on large-scale genomic structure (>20 markers) rather than selecting a number of groups based on prior expectations.…”
Section: Development Of a Genetic Linkage Mapmentioning
confidence: 80%
See 1 more Smart Citation
“…Of the 1,430 HQ SNPs used for linkage analysis, we were able to assign most (87%) to linkage groups with high confidence (LOD scores ≥ 8). Most of the mapped markers (998, or 81% of mapped markers) were captured in the 16 largest linkage groups (LGs), a biologically plausible number comparable to the range of haploid chromosome numbers (n) reported in other Scleractinian corals (n = 14-27; [67][68][69]). Because chromosome numbers have not been directly determined in O. faveolata, we included all linkage groups containing sufficient markers to provide meaningful information on large-scale genomic structure (>20 markers) rather than selecting a number of groups based on prior expectations.…”
Section: Development Of a Genetic Linkage Mapmentioning
confidence: 80%
“…While the haploid number of chromosomes in O. faveolata has not been empirically determined, our analysis of recombination frequencies identified 16 linkage groups that we hypothesize represent chromosomes or portions of chromosomes. For comparison, data on haploid chromosome numbers (karyotype) are available for multiple (31) coral species [20,[69][70][71][72], and these range from n=12 to n=27 across all Scleractinian corals measured. The Scleractinian phylogeny includes two major clades (called robust and complex) that probably diverged >240 mya [73].…”
Section: Discussionmentioning
confidence: 99%
“…The corresponding system determinations are poorly known: a few ESD examples have been reported but no examples of GSD have so far been confirmed among non-bilaterians [6]. A cytogenetic analysis has shown a clear evidence of potential sex chromosomes in a scleractinian [7] but the role of these chromosomes in sex determination remains to be studied as this species is hermaphroditic. Gonochorism is highly predominant in octocorals (89% of the species [8]), even if cases of rapid transition between gonochorism and hermaphrodism have been demonstrated in the genus Alcyonium  [9].…”
Section: Introductionmentioning
confidence: 99%
“…To solve the controversial taxonomic issue (Fukami et al 2004) and develop an understanding of coral genetics, we have been accumulating molecular cytogenetic data of scleractinian corals. So far, we have published three molecular cytogenetic reports using FISH on scleractinian corals, such as A. solitaryensis, E. aspera, and C. aspera (Taguchi et al 2013(Taguchi et al , 2014(Taguchi et al , 2016, which are commonly found on the western coast of Japan (Wallace 1999). The present study is our fourth report and concerns P. contorta; it is a different genus from our previous studies but is classified in the same family Merulinidae with C. aspera.…”
Section: Discussionmentioning
confidence: 60%
“…So far, we have reported molecular cytogenetic information on three species of stony corals, such as Acropora solitaryensis (family Acroporidae), Coleostrea aspera (family Merulinidae), and Echinophillia aspera (family Lobophylliidae). Our studies on these three species have led to several new findings, such as precise and consistent numbers of chromosomes, rRNA gene loci, and the presence of a homogenously staining region (hsr), consisting of rDNA and some coral repeated sequences shared with humans (Taguchi et al 2013(Taguchi et al , 2014(Taguchi et al , 2016.…”
mentioning
confidence: 99%